Emphasizing the Thinking and Scientific Language in the Primary Classes - Saleh Y. Abo-Romi (New Horizons in Education and Social Studies Vol. 9, 2021)
According to psychological and cognitive development theories, the preferences of pupils in elementary school toward inductive versus deductive and general types of reasoning when asked to prove or review mathematical claims, changes along the school years. One of elementary school’s curricular goals is to foster critical thinking skills in students. This study examines this hypothesis through a survey in which 267 pupils from the Arabic sector in three different elementary schools in Israel, in grades 4 to 6 participated. The survey, based on the math reasoning tasks by Healy and Hoyles [1], is comprised of Algebra and Geometry reasoning tasks. Additionally, 12 of these pupils’ teachers were interviewed in order to explore their attitudes toward mathematical reasoning and math proving tasks. Findings show that: 1) There is a difference in students’ preferences towards types of reasoning, between grades 4 and 6; 2) Sixth graders will be less likely to accept tautologic and inductive reasoning than fourth graders; 3) Elementary school pupils tend to prefer empirical arguments (such as inductive and example-based) as their approach in contrast to the arguments that they believe will receive the highest scores from their teachers. However, findings do not support the hypothesis that there will be a difference in teachers’ preferences towards different types of thinking. The research findings and their practical implications are discussed. The findings of the present study indicate that the process is not as linear and unidirectional as Piaget’s theory might suggest. Therefore, the descriptive framework proposed in this study may help to somewhat alleviate the contradiction some teachers may experience in the classroom.